Socioeconomic disadvantage and polygenic risk for high BMI magnify obesity risk across childhood: a longitudinal, population, cohort study. (March 2023) - Kerr, Jessica A; Dumuid, Dorothea; Downes, Marnie; Lange, Katherine; O'Connor, Meredith; Thornton, Lukar; Mavoa, Suzanne; Lycett, Kate; Olds, Tim S; Edwards, Ben; O'Sullivan, Justin M; Juonala, Markus; et al.
Abstract: Background: Across the life course, socioeconomic disadvantage disproportionately afflicts those with genetic predispositions to inflammatory diseases. We describe how socioeconomic disadvantage and polygenic risk for high BMI magnify the risk of obesity across childhood, and using causal analyses, explore the hypothetical impact of intervening on socioeconomic disadvantage to reduce adolescent obesity. Methods: Data were drawn from a nationally representative Australian birth cohort, with biennial data collection between 2004 and 2018 (research and ethics committee approved). We generated a polygenic risk score for BMI using published genome-wide association studies. We measured early-childhood disadvantage (age 2–3 years) with a neighbourhood census-based measure and a family-level composite of parent income, occupation, and education. We used generalised linear regression (Poisson-log link) to estimate the risk of overweight or obesity (BMI ≥85th percentile) at age 14–15 years for children with early-childhood disadvantage (quintiles 4–5) versus average (quintile 3) and least disadvantage (quintiles 1–2), for those with high and low polygenic risk separately. Findings: For 1607 children (n=796 female, n=811 male; 31% of the original cohort [N=5107]), polygenic risk and disadvantage were both associated with overweight or obesity; effects of disadvantage were more marked as polygenic risk increased. Of children with polygenic risk higher than the median (n=805), 37% of children living in disadvantage at age 2–3 years had an overweight or obese BMI by adolescence, compared with 26% of those with least disadvantage. For genetically vulnerable children, causal analyses indicated that early neighbourhood intervention to lessen disadvantage (to quintile 1–2) would reduce risk of adolescent overweight or obesity by 23% (risk ratio 0·77; 95% CI 0·57–1·04); estimates for improving family environments were similar (0·59; 0·43–0·80). Interpretation: Actions addressing socioeconomic disadvantage could mitigate polygenic risk for developing obesity. This study benefits from population-representative longitudinal data but is limited by sample size. Funding: Australian National Health and Medical Research Council.